Periodic Exposure of Keratinocytes to Cold Physical Plasma: An In Vitro Model for Redox-Related Diseases of the Skin. (4th February 2016) - Schmidt, Anke; von Woedtke, Thomas; Bekeschus, Sander
Abstract : Oxidative stress illustrates an imbalance between radical formation and removal. Frequent redox stress is critically involved in many human pathologies including cancer, psoriasis, and chronic wounds. However, reactive species pursue a dual role being involved in signaling on the one hand and oxidative damage on the other. Using a HaCaT keratinocyte cell culture model, we investigated redox regulation and inflammation to periodic, low-dose oxidative stress after two, six, eight, ten, and twelve weeks. Chronic redox stress was generated by recurrent incubation with cold physical plasma-treated cell culture medium. Using transcriptome microarray technology, we identified both acute ROS-stress responses as well as numerous adaptions after several weeks of redox challenge. We determined a differential expression (2-fold, FDR < 0.01, p < 0.05 ) of 260 genes that function in inflammation and redox homeostasis, such as cytokines (e.g., IL-6, IL-8, and IL-10), growth factors (e.g., CSF2, FGF, and IGF-2), and antioxidant enzymes (e.g., HMOX, NQO1, GPX, and PRDX). Apoptotic signaling was affected rather modestly, especially in p53 downstream targets (e.g., BCL2, BBC3, and GADD45). Strikingly, the cell-protective heat shock protein HSP27 was strongly upregulated (p < 0.001 ). These results suggested cellular adaptions to frequent redox stress and may help to better understand the inflammatory responses in redox-related diseases.